A Review For Water Monitoring Based on Invasive Aquatic Plants - Bala Santaran, Arivarasan; Seswoya, Roslinda (Recent Trends in Civil Engineering and Built Environment, 2021)
Invasive aquatic plant is non-native aquatic plant species which be prone to grow more rapid than the original native species even in habitats that have low resources, due to its high level of adaptation when accompanied with an absence of common predators. The aquatic invasive plants have been introduced in many new habitats intentionally and unintentionally. These plants easily reproduce and increase its population starting from small fragments. The emergent, free-floating, and submerged aquatic invasive plants successfully invades to new habitats and causes various impacts towards socio-economy, freshwater ecosystem and water quality. The physical, biological and chemical control methods are considered for managing the aquatic invasive plants. Few researchers have studied the water quality parameters with the presence of aquatic invasive plants. This review summarizes information about the categories of aquatic invasive plants, the process and factors of successful invasion, the impacts of invasive plants management methods to control aquatic invasive plants, the relationship between water quality parameters and the presence of invasive aquatic plants.